Isolated persistent left-sided superior vena cava in a patient with end-stage kidney disease - Naidoo, Poobalan; Ramkisson, Nischal; Mody, Kalpesh Giresh; Leisegang, Rory Forseth; Naidoo, Yeshkhir; Hariparshad, Sudesh Premchund; Assounga, Alain Guy Honore (African Journal of Nephrology, 2024)
An adult male of Asian origin with end-stage kidney disease secondary to diabetic nephropathy, was found to have a persistent left-sided superior vena cava (PLSVC) that drained into the coronary sinus, without an associated right-sided SVC, following the placement of a haemodialysis catheter. A persistent left-sided SVC arises from the failure of obliteration of the embryological left anterior cardinal vein. It is a rare finding and is usually asymptomatic. Given that nephrologists manage patients who may require vascular access, knowledge of the possibility of vascular anomalies may assist in preventing vascular injuries. Guidewires and dilators should be handled with utmost care to prevent vascular injury and the risk of cardiac rupture. Routine imaging should be performed to evaluate the position and course of central venous catheters after insertion so that vascular anomalies such as PLSVC can be identified timeously.